Nikolai Tarabukin at the State Academy of Artistic Sciences: The Problem of Style - Ivanova, Ekaterina (Wiener Slawistischer Almanach, 2026)
This article examines Nikolai Tarabukin’s work in the field of art theory during the years of his affiliation with the State Academy for Artistic Research (GAKhN). This period was marked, among other things, by significant changes in Tarabukin’s views on art: from the avant-garde theory of Productivist art he moved toward a sharply critical stance toward the newest left-wing artistic movements. The most striking expression of this shift can be found in his original conception of style, namely in his stylistic interpretation of artistic genres, which Tarabukin developed throughout the second half of the 1920s. The examination of this conception constitutes the central focus of the present article. In addition to Tarabukin’s published writings, the study draws on extensive archival materials and unpublished manuscripts, while also situating his ideas within the broader intellectual context of the period. Through this approach, the reconstruction of Tarabukin’s conception emerges as a revealing case study of the effort to define artistic terminology, as well as of the ideological assumptions that may have underlain this fundamental task.